Similarities of International Humanitarian Law and Islamic Law of Warfare: An Appraisal of The Principle of Distinction During Armed Conflict - Haruna, Abdulrashid Lawan (Journal of Malaysian and Comparative Law, 2018)
Principle of distinction obliges belligerents to always distinguish between combatants and civilians and between civilian objects and military objectives, and shall accordingly direct their military operations only against military objectives. The principle is derived from humanity as such it is one of the basic and fundamental rules guiding the conduct of hostilities under International Humanitarian Law (IHL) and Islamic Law of Warfare. The essence of the principle of distinction is to secure civilian population and their objects from the risks and dangers of attack in conduct of hostilities. Notwithstanding the significance of the principle, belligerents often fail to adhere to this principle thereby resulting in wanton killing of civilians and destruction of civilian objects. This has influenced the perception of some people towards the existence of such humanitarian principle under Islamic law, especially in conflicts that have religious elements. Thus, it is imperative that the article examines the principle within the legal framework of IHL and Islamic Law of Warfare in order to bring to light the platform for its effective application by both states and armed groups during armed conflicts.